Discovery of Brominated Alboflavusins With Anti-MRSA Activities - Li, Chao; Bao, Wuyundalai; Zhang, Haoyue; Lyu, Zhitang; Chen, Yihua; Guo, Zhengyan (Frontiers in Microbiology, 2021)
As Methicillin-resistant Staphylococcus aureus (MRSA) is becoming a serious pathogenic threaten to human health worldwide, there is an urgent need to discover new antibiotics for the treatment of MRSA infections. Alboflavusins (AFNs) are a group of halogenated cyclohexpeptides with anti-MRSA activities. In this study, two novel brominated AFN congeners (compounds 1 and 2) were isolated from the wild-type strain Streptomyces alboflavus sp. 313 that was fermented in the production medium supplemented with NaBr; two new (compounds 3 and 5) and a known (compound 4) dehelogenated AFN congeners were isolated from S. alboflavusΔafnX, in which the tryptophan halogenase gene afnX was inactivated. The structures of these compounds were assigned by careful NMR and MS analyses. The anti-MRSA activities of varied AFN congeners were assessed against different MRSA strains, which revealed that compounds 1 and 2 with bromine displayed effective activities against the tested MRSA strains. Especially, compound 2 showed good anti-MRSA activity, while compounds 3, 4, and 5 without halogen exhibited weak anti-MRSA activities, outlining the influence of halogen substitution to the bioactivities of AFNs.